Assessing the impact of hepatitis B immunization in over 5 year olds from selected province of South Africa - Amponsah-Dacosta, Edina (My University, 2014)
Introduction: The hepatitis B virus (HBV) causes a serious type of liver disease referred to as hepatitis B, which is associated with various fatal sequelae following the onset of chronic infection. As a result of the global burden of chronic HBV infection, HBV-related mortality is currently estimated at 620 000 annual deaths worldwide (Hwang and Cheung, 2011). The World Health Assembly (WHA) recommended in 1992 that the hepatitis B vaccine be incorporated into national immunization programmes universally, especially in the hyperendemic regions of the world, in order to curb the global burden of hepatitis B (WHO, 1992). Accordingly, South Africa introduced the hepatitis B vaccine into the national Expanded Programme on Immunization (EPI-SA) in April 1995. Almost 17 years later, South Africa has not conducted any nationwide serosurveys to monitor the population impact of the hepatitis B vaccine. Instead, a number of field and laboratory studies have been conducted only in vaccinated children within the first 5 years of life and as such reports on the short¬term impact made by the hepatitis B vaccine in the country have largely relied on these studies (Tsebe et al., 2001; Schoub et al., 2002; Simani et al., 2008). The aim of the current study therefore was to assess the population impact made by the hepatitis B vaccine post its introduction into EPI-SA using an age stratified, cross-sectional study. The objectives were to compare the prevalence of HBV exposure between the post- and pre-vaccination populations of South Africa, determine the influence of HIV infection on the prevalence of HBV exposure between the post- and pre-vaccination populations of South Africa by performing a subset analyses, and lastly, to perform molecular characterization of hepatitis B surface and polymerase genes in HBV DNA positive individuals. Materials and Methods: This was an explorative and descriptive retrospective, cross¬ sectional study based on recently tested and stored blood samples from the NHLS fi Diagnostic Laboratory in the Department of Virology. For the purpose of this study, these samples were obtained after Ethics approval, and two target populations identified based on the year (Le. 1995) the hepatitis B vaccine was introduced into EPI-SA; a post-vaccination population consisting of 605 blood samples from individuals aged 1-15 years and a pre¬vaccination population consisting of 601 blood samples from individuals aged 16-25 years. The post-vaccination population was further stratified by age as follows; 1-5,6-10 and 11-15 years, in order to assess immunity and chronic carriage of HBV across the different age groups. All samples were tested for the following primary serological markers; HBsAg, anti¬HBc and anti-HBs, to determine the prevalence of HBV chronic carriage, past HBV exposure and immunity to HBV infection respectively. Samples were further assessed for the vi incidence of acute HBV infection by testing for IgM anti-HBc. All serological testing was performed using the Elecsys@ 2010 Immunoassay System. Samples with serological evidence of infection or exposure to HBV were selected and screened for HBV DNA using a real time PCR assay to determine the prevalence of active HBV infection within this group. Study subjects with records of their HIV status, either positive or negative, were also pooled for subset analyses in order to determine the influence of HIV infection on immunity and chronic carriage of HBV. Finally, samples positive for HBV DNA were subjected to molecular characterization of the hepatitis B surface (S) and polymerase (pol) genes. Results: Following serological screening, immunity to HBV infection was found to be significantly (p<0.001) higher (56.7%) in the post-vaccination population than in the pre-vaccination population (15.5%). Within the post-vaccination population alone, immunity was found to wane with increasing age from 76.1 % in those 1-5 years of age to 50.0% in those 6-10 years and 44.2% in those 11-15 years of age. Chronic carriage on the other hand was significantly (p=0.008) reduced in the post-vaccination population with 1.5% HBsAg prevalence as compared to 4.0% in the pre-vaccination population. Within the different age strata, chronic carriage increased with increasing age (0.5% in 1-5 years; 1.3% in 6-10 years; 2.5% in 11-15 years). Overall, no acute HBV infection was detected within the post-vaccination population, while a 14.6% prevalence rate of acute HBV infection was found for the pre-vaccination population. From the subset analyses, immunity was found to be significantly (p<0.001) higher in the HIV uninfected population as compared to the HIV infected population; 82.5% versus 22.0% in the post-vaccination population and 26.7% versus 0% in the pre-vaccination population, while chronic carriage was found to be higher in the HIV infected population than in the HIV uninfected population. Following molecular characterization of the HBV S gene, it was revealed that the majority of the viral isolates were genotype A, with only 1 genotype D isolate found. A number of notable amino acid i$ variations were also detected within the antigenic region of the HBsAg of viral isolates, inCluding the K122R, N131T, T143S, and E164D mutations. Conclusion: Introduction of the hepatitis B vaccine into EPI-SA has shown remarkable success in children under the age of 5 years. Overall, immunity and chronic carriage of HBV within the post-vaccination population has been greatly impacted by hepatitis B immunization. Within the HIV infected population, susceptibility to HBV infection remains a cause for concern. Finally, although amino acid variations within the viral HBsAg are present, vaccine escape-related mutants appear to be rare or even absent within the South African population. vii
Thesis (M Med (Virology))-- University of Limpopo (Medunsa Campus), 2013
Keywords: Hepatitis B; Hepatitis